2021
DOI: 10.3390/cells10071615
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of the Coin: Mast Cells as a Key Regulator of Allergy and Acute/Chronic Inflammation

Abstract: It is well known that mast cells (MCs) initiate type I allergic reactions and inflammation in a quick response to the various stimulants, including—but not limited to—allergens, pathogen-associated molecular patterns (PAMPs), and damage-associated molecular patterns (DAMPs). MCs highly express receptors of these ligands and proteases (e.g., tryptase, chymase) and cytokines (TNF), and other granular components (e.g., histamine and serotonin) and aggravate the allergic reaction and inflammation. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 147 publications
(214 reference statements)
0
35
0
Order By: Relevance
“…Food-induced microbiome changes and allergic immune activation are thought to affect brain function through neuroimmune interactions, which can affect the enteric nervous system and central nervous system and eventually lead to neurodevelopmental abnormalities [ 44 ]. Fourth, inflammatory cytokines produced in allergic conditions could lead to altered metabolism of norepinephrine and dopamine, which was considered a critical neurological change in ADHD pathology [ 36 , 45 ]. Lastly, it is also possible that there is a shared cause leading to both allergic conditions and ADHD or a bidirectional association between allergic conditions and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Food-induced microbiome changes and allergic immune activation are thought to affect brain function through neuroimmune interactions, which can affect the enteric nervous system and central nervous system and eventually lead to neurodevelopmental abnormalities [ 44 ]. Fourth, inflammatory cytokines produced in allergic conditions could lead to altered metabolism of norepinephrine and dopamine, which was considered a critical neurological change in ADHD pathology [ 36 , 45 ]. Lastly, it is also possible that there is a shared cause leading to both allergic conditions and ADHD or a bidirectional association between allergic conditions and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-10 is a well-known immunosuppressive cytokine produced by Tregs, it also plays an important role in the differentiation and functional capacity of Tregs themselves [102,103]. Takasato et al [104,105] have demonstrated a helpful effect of MMCs in OIT using a mouse model of OIT. OIT shifted MMCs from pathogenic (or pro-allergic) status to regulatory (desensitization) status.…”
Section: Helpful Effects Of Mmcsmentioning
confidence: 99%
“…MCs influence inflammation, fibrosis, the gastrointestinal and reproductive tracts, hemostasis, the and cardiovascular system [ 17 ], and their disturbances are classified as secondary MC disorders, often influenced by interleukin (IL)-3, IL-4, IL-9, IL-10, IL-33, TGF-β, SCF and many other agents ( Figure 1 ) [ 21 ]. In recent years, significantly more is known about their regulatory, physiological function, such as wound healing, immune tolerance, and suppression of allergies, and not just their pathological involvement [ 3 ].…”
Section: Mast Cell Disordersmentioning
confidence: 99%
“…The IgE-dependent pathway is considered as the main one for MC physiological activation in host defense against parasitic infections and the initiation of type I allergic reactions [ 23 ] and requires sensitization to an allergen. On the other hand, IgE-independent pathways have also been proven to serve pivotal roles in the pathophysiology of allergic and pseudoallergic responses but include MC activation by inflammatory mediators, complement fragments, cytokines, and neuropeptide substance P through specific G-protein-coupled receptors (GPCR) [ 3 ].…”
Section: Mast Cell Disordersmentioning
confidence: 99%
See 1 more Smart Citation